4) \( \begin{array}{l}n(a)=3 a+2 \\ f(a)=2 a-4 \\ \text { Find }\left(\frac{g}{f}\right)(3)\end{array} \) (3)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \(\left(\frac{g}{f}\right)(3)\), we need to clarify what \(g(a)\) is. However, given \(n(a)\) and \(f(a)\), it appears that we should derive a function \(g(a)\) or at least understand the ratio in context. First, let's calculate \(f(3)\): \[ f(3) = 2(3) - 4 = 6 - 4 = 2. \] If we assume \(g(a) = n(a)\), we find: \[ n(3) = 3(3) + 2 = 9 + 2 = 11. \] Now we can compute \(\left(\frac{g}{f}\right)(3)\): \[ \left(\frac{g}{f}\right)(3) = \frac{g(3)}{f(3)} = \frac{n(3)}{f(3)} = \frac{11}{2}. \] Thus, the final result is: \[ \left(\frac{g}{f}\right)(3) = \frac{11}{2}. \]